2017
DOI: 10.1103/physreva.95.042322
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of heterodyning over homodyning: An assessment with quadrature moments

Abstract: We examine the moment-reconstruction performance of both the homodyne and heterodyne (doublehomodyne) measurement schemes for arbitrary quantum states and introduce moment estimators that optimize the respective schemes for any given data. In the large-data limit, these estimators are as efficient as the maximum-likelihood estimators. We then illustrate the superiority of the heterodyne measurement for the reconstruction of the first and second moments by analyzing Gaussian states and many other significant no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…Given the CM (24) it is straightforward to calculate the second-order correlation function g (2) TM (0) of the corresponding state ρ ab in Eq. (23). The analytical formula is clumsy and it is not reported explicitly in its general form.…”
Section: Two-mode Gaussian Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the CM (24) it is straightforward to calculate the second-order correlation function g (2) TM (0) of the corresponding state ρ ab in Eq. (23). The analytical formula is clumsy and it is not reported explicitly in its general form.…”
Section: Two-mode Gaussian Statesmentioning
confidence: 99%
“…In particular, if we set ψ = π we can still find the threshold values of the coherent amplitudes α and β and of the thermal contributions N th,1 and N th,2 , in order to have g TM of two-mode Gaussian states as a function of the displacement amplitudes α and β in the case of the TMSTS given in Eq. (23) with N th,1 = N th,2 = 0 (left panel) and N th,1 = N th,2 = 0.15 (right panel). In both the panels we set r = 0.5 and ψ = π, where ξ = r e iψ is the two-mode squeezing parameter, see the text for details.…”
Section: Two-mode Gaussian Statesmentioning
confidence: 99%
“…That HET surpasses BHOMOPT for the m = 1 case for any state is a consequence of the Heisenberg-Robertson-Schrödinger uncertainty relation [32]. The limiting case where the two methods give identical sCRBs is when the state is of minimum uncertainty.…”
mentioning
confidence: 94%
“…Therefore, sCRB BHOMOPT for any state using this improved reconstruction strategy can be obtained through the Fisher information of the homodyne parameter X m ϑ . The theory for this was developed in [32]. It shall be shown that in practice, UHOM is tomographically more powerful than all other methods for moment tomography of interesting states, which forms the second main result.…”
mentioning
confidence: 99%
See 1 more Smart Citation